DOUBLE DIP PANDEMIC IMPACT ON PORTFOLIO OF INVESTORS REFERENCE TO SALARIED EMPLOYEES - Reddy, P. Madhu Kumar; Kandi, V S Prasad; Kumar, A. Rama (Indian Journal of Finance and Banking, 2022)
The ongoing health crisis around COVID -19 has affected all communities. The Government has taken action since the Coronavirus attack created an unprecedented situation. Drop-down COVID-19 positive cases in December and January made people to normal life. An immediate double-dip from the COVID-19, plow back them into hazardous life with more effective and more quickly spreading of virus leads to the second lockdown. The present study analyzed different investments avenues and the factors that affect the investment. The main objective of the study is to know the relationship between the re-entry of COVID-19 and the change in investment decisions of the salaried employees in Telangana. The study also identifies the investor’s attitude towards Mutual Funds and understands how the second wave COVID-19 has impacted on investments and financial decisions of individuals in developing nations such as India. JEL Classification Codes: G01, G11, G40, G41, G51.